Brain natriuretic peptide and acute hypobaric hypoxia in humans - Woods, David; Hooper, Tim; Mellor, Adrian; Hodkinson, Pete; Wakeford, Rob; Peaston, Bob; Ball, Steve; Green, Nic (The journal of physiological sciences, 2011)
In animal models, the secretion of the cardiac hormone, brain natriuretic peptide (BNP), and its closely related peptide, atrial natriuretic peptide (ANP), are stimulated by acute hypoxia. There is extensive human evidence for a rise in ANP under acute hypoxic conditions but very little evidence regarding the BNP response to acute hypoxia in humans. We therefore subjected seven healthy subjects to an acute hypobaric hypoxic stimulus to examine if BNP secretion increases rapidly. Significant hypoxaemia (mean nadir oxygen saturation 62.3%) was induced but no significant rise in BNP occurred. This suggests that either such acute hypoxaemia is well tolerated by the healthy human heart or it is not a stimulus for BNP secretion.